Historical Agriculture and Soil Erosion in the Upper Mississippi Valley Hill Country - Trimble, Stanley W. (Taylor & Francis, 2013)
"This thought-provoking book demonstrates how processes of landscape transformation, usually illustrated only in simplified or idealized form, play out over time in real, complex landscapes. Trimble illustrates how a simple landscape disturbance, generated in this case by agriculture, can spread an astonishing variety of altered hydrologic and sedi